Solar hydrogen production : processes, systems and technologies - Calise, Francesco; Dentice D'Accadia, Massimo; Santarelli, Massimo; Lanzini, Andrea; Ferrero, Domenico (Academic Press, an imprint of Elsevier, 2019)
Solar Hydrogen Production: Processes, Systems and Technologies presents the most recent developments in solar-driven hydrogen generation methods. The book covers different hydrogen production routes, from renewable sources, to solar harvesting technologies. Sections focus on solar energy, presenting the main thermal and electrical technologies suitable for possible integration into solar-based hydrogen production systems and present a thorough examination of solar hydrogen technologies, ranging from solar-driven water electrolysis and solar thermal methods, to photo-catalytic and biological processes. All hydrogen-based technologies are covered, including data regarding the state-of-the art of each process in terms of costs, efficiency, measured parameters, experimental analyses, and demonstration projects. In the last part of the book, the role of hydrogen in the integration of renewable sources in electric grids, transportation sector, and end-user applications is assessed, considering their current status and future perspectives. The book includes performance data, tables, models and references to available standards. It is thus a key-resource for engineering researchers and scientists, in both academic and industrial contexts, involved in designing, planning and developing solar hydrogen systems. --